Impact of phase I metabolism on uptake, oxidative stress and genotoxicity of the emerging mycotoxin alternariol and its monomethyl ether in esophageal cells - Tiessen, Christine (Arch Toxicol, 2016)
Studies on the genotoxicity of Alternaria mycotoxins focus primarily on the native compounds. Alternariol (AOH) and its methyl ether (AME) have been reported to represent substrates for cytochrome P450 enzymes, generating hydroxylated metabolites. The impact of these phase I metabolites on genotoxicity remains unknown. In the present study, the synthesis and the toxicological effects of the metabolites 4-hydroxy alternariol (4-OH-AOH) and 4-hydroxy alternariol monomethyl ether (4-OH-AME) are presented and compared to the effects of the parent molecules. Although the two phase I metabolites contain a catecholic structure, which is expected to be involved in redox cycling, only 4-OH-AOH increased reactive oxygen species (ROS) in human esophageal cells (KYSE510), 4 times more pronounced than AOH. No ROS induction was observed for 4-OH-AME, although the parent compound showed some minor impact. Under cell-free conditions, both metabolites inhibited topoisomerase II activity comparable to their parent compounds. In KYSE510 cells, both metabolites were found to enhance the level of transient DNA–topoisomerase complexes in the ICE assay. Although the level of ROS was significantly increased by 4-OH-AOH, neither DNA strand breaks nor enhanced levels of formamidopyrimidine-DNA-glycosylase (FPG)-sensitive sites were observed. In contrast, AOH induced significant DNA damage in KYSE510 cells. Less pronounced or even absent effects of hydroxylated metabolites compared to the parent compounds might at least partly be explained by their poor cellular uptake. Glucuronidation as well as sulfation appear to have only a minor influence. Instead, methylation of 4-OH-AOH seems to be the preferred way of metabolism in KYSE510 cells, whereby the toxicological relevance of the methylation product remains to be clarified. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00204-016-1801-0) contains supplementary material, which is available to authorized users.